Dynamic response of wind turbine gear system with uncertain-but-bounded parameters using interval analysis method. (December 2017) - Guerine, A.; El Hami, A.; Walha, L.; Fakhfakh, T.; Haddar, M.
Abstract: In this paper, we propose the interval analysis method for the dynamic response of wind turbine gear system with uncertain-but-bounded parameters. We developed a lumped dynamic model with 8dofs. Lagrange formalism is used to formulate the governing equation of motion of the model. The simulation results are obtained by the interval analysis method for dynamic analysis under uncertainty. The interval analysis method results are compared with probabilistic approach results. This kind of results is coincident with the meaning of the probabilistic approach and interval analysis method.